A BUSINESS FEASIBILITY ANALYSIS OF SMALL AND MEDIUM ENTERPRISES FOR PRODUCT STRATEGY DETERMINATION - Franka Hendra; Supriyono Supriyono; Riki Efendi; Rosalinda Rosalinda; Retno Indriyati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
The main objective of this research is to analyze the feasibility of a small and medium enteIDRrise to analyze the feasibility of developing its business. The method used in this paper is to determine a slow skimming strategy by first analyzing financial feasibility and analyzing internal and external factors. The results of this study are that the slow skiming strategy is implemented by concentrating efforts in certain places that are relatively limited and areas that are still close to the company's location, introducing products by carrying out promotional activities at every event or exhibition, consumers are willing to pay for products because of friendliness in service and satisfaction. With regard to products